Hemodynamic Factors Driving Peripheral Chemoreceptor Hypersensitivity: Is Severe Aortic Stenosis Treated with Transcatheter Aortic Valve Implantation a Valuable Human Model? - Maksym Jura; Stanisław Tubek; Jędrzej Reczuch; Rafał Seredyński; Piotr Niewiński; Marcin Protasiewicz; Beata Ponikowska; Bartłomiej Paleczny (Biomedicines)
Background: A reduction in carotid artery blood flow (CABF) and ultimately in wall shear stress (WSS) is a major driver of heightened peripheral chemoreceptor (PCh) activity in animal models of heart failure. However, it is yet to be translated to humans. To provide more insight into this matter, we considered severe aortic stenosis (AS) before and after transcatheter aortic valve implantation (TAVI) as a human model of carotid and aortic body function under dramatically different hemodynamic conditions. Materials and Methods: A total of 26 severe AS patients (aged 77 ± 6 y, body mass index: 29.1 ± 5.1 kg/m2, left ventricular ejection fraction (LVEF): 50 ± 15%) were subjected to a transient hypoxia test twice: immediately before vs. 1–4 months after TAVI (median follow-up: 95 days). PCh function was analyzed in terms of ventilatory (HVR, L/min/SpO2%) and heart rate responses to hypoxia (HR slope, bpm/SpO2%). Standard ultrasound (inc. aortic valve area [AVA], mean aortic valve gradient, peak aortic jet velocity, LVEF, and CABF), respiratory, hemodynamic, and blood parameters were collected at both visits. Pre- vs. post-TAVI data regarding HVR and HR slopes were available for N = 26 and N = 10 patients, respectively. Results: HVR did not change following TAVI (pre- vs. post-TAVI: 0.42 ± 0.29 vs. 0.39 ± 0.33 L/min/SpO2%, p = 0.523). The HR slope increased after TAVI (pre- vs. post-TAVI: 0.26 ± 0.23 vs. 0.37 ± 0.30 bpm/SpO2%, p = 0.019), and the magnitude of the increase was strongly associated with an increase in AVA (Spearman’s R = 0.80, p = 0.006). No other significant relations between pre- vs. post-TAVI changes in PCh activity measures vs. hemodynamic parameters were found (all p > 0.12). Conclusions: The ventilatory component of the PCh reflex (defined as HVR) in severe AS patients is not affected by TAVI, and pre-TAVI values in this group are fairly comparable to those reported previously for healthy subjects. On the contrary, HR responses to hypoxia are increased after TAVI, and pre-TAVI values appear to be lower compared to the healthy population. An extraordinarily strong correlation between post-TAVI increases in HR slope and AVA may suggest that hemodynamic repercussions of the surgery in the aortic body area (most likely reduced WSS) play a critical role in determining aortic body function with a negligible effect on the carotid bodies. However, caution is needed when interpreting the results of the HR response to hypoxia in our study due to the small sample size (N = 10).